2014
DOI: 10.1186/s12918-014-0106-2
|View full text |Cite
|
Sign up to set email alerts
|

Membrane related dynamics and the formation of actin in cells growing on micro-topographies: a spatial computational model

Abstract: BackgroundIntra-cellular processes of cells at the interface to an implant surface are influenced significantly by their extra-cellular surrounding. Specifically, when growing osteoblasts on titanium surfaces with regular micro-ranged geometry, filaments are shorter, less aligned and they concentrate at the top of the geometric structures. Changes to the cytoskeleton network, i. e., its localization, alignment, orientation, and lengths of the filaments, as well as the overall concentration and distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Osteoblasts lose a large part of their cell organelles but gain long, thin, and branched cell processes by which the cells remain in contact with neighboring osteocytes, capillaries, and osteoblasts lining the bone surface. Osteogenic cells have a highly developed cytoskeleton, and it is known that their differentiation is regulated in part through mechanical forces imposed by their surrounding environment [35][36][37].…”
Section: Assessment Of Osteoblast Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoblasts lose a large part of their cell organelles but gain long, thin, and branched cell processes by which the cells remain in contact with neighboring osteocytes, capillaries, and osteoblasts lining the bone surface. Osteogenic cells have a highly developed cytoskeleton, and it is known that their differentiation is regulated in part through mechanical forces imposed by their surrounding environment [35][36][37].…”
Section: Assessment Of Osteoblast Behaviormentioning
confidence: 99%
“…In non-migrating cells, mature large FAs can be formed or even localized in the cell body during migration. They are predominantly composed of vinculin, paxilin, α actinin, and FAKs (Focal Adhesion Kinases) [35,36,43,44].…”
Section: Assessment Of Osteoblast Behaviormentioning
confidence: 99%
“…Spatiotemporal regulation of tension sustained at FAs has been described as essential for the regulation of cell migration and settlement pointing to extracellular matrix remodeling and new bone formation. Force-mediated FA signaling together with actin bundles organization in stress fibers regulates cell proliferation and differentiation [ 78 , 79 , 80 , 81 , 82 , 83 ]. Actin cytoskeleton immunolabelling in HOB ® , after 48 h in culture in the presence of SCS8T10_U, revealed that the osteoblasts were big, some of them elongated, with filopodial and lamellipodial emissions.…”
Section: Resultsmentioning
confidence: 99%
“…Alternative methods for specifying models include languages/formats with syntactic differences that tend to offer similar functionality [58, 62, 99, 100]; domain-specific languages that offer higher-level abstractions that can ease the task of model specification [101]; and embedded languages, which allow a modeler to leverage the power of a general-purpose programming language [69]. There are also BNGL extensions and other languages that enable modeling capabilities beyond what is available within the BNGL framework [67, 68, 102107]. We note that rules and rule-based models are readily visualized [7678, 93, 96, 105, 108, 109] and software tools exist that enable a visual approach to model specification, such as RuleBuilder [75] and Simmune [63, 104, 105].…”
Section: Methodsmentioning
confidence: 99%